UNVEILING GREEN INTENTIONS: THE INTERPLAY OF PERCEIVED VALUE AND PRODUCT TRUST AMONG CHINESE CONSUMERS - ZHANG, Jie; Bunchapattanasakda, Chanchai (Asian Interdisciplinary and Sustainability Review, 2025)
This study examines the drivers of green consumption intentions among Chinese consumers, focusing on the interplay between perceived value and product trust within the context of organic food. Guided by the Appraisal-Emotional Response-Coping framework, we analyze survey data from 398 participants using structural equation modeling (SEM). Findings reveal significant direct impacts of functional, emotional, and social value on green purchase intentions. Furthermore, product trust emerges as a critical mediator, strengthening consumer confidence in environmental claims and the reliability of sustainable products, thereby fostering the relationship between perceived value and purchase behavior. The results enrich theoretical understandings of sustainable consumer behavior and offer actionable insights for practitioners. Recommended strategies include transparent labeling of sustainability attributes, emotional marketing that emphasizes ethical advantages, social media initiatives that leverage peer influences, and rigorous certification standards. The study highlights the nuanced role of cultural context and consumer trust in promoting sustainable consumption, providing valuable implications for targeted marketing strategies.